The Influence of Motivation, Workload, and Work Environment on Teacher Performance Through Organizational Citizenship Behavior (OCB) at the Darus Sa'adah Islamic Education Foundation Jember - Rifky, Moh. Yanuar (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This study aims to empirically examine the variables in the research that have been formulated in the formulation of the problem, namely whether there is an influence of motivation (X1) workload (X2) and work environment (X3) on performance (Y) through Organizational Citizenship Behavior (Z) at Darus Sa'adah Islamic Education Foundation Jember. This study uses a quantitative method with an explanatory research approach with a sample of 50 respondents. The results of the analysis show that the effect of motivation on (OCB) with a direct influence path coefficient of 0.290, then workload affects on (OCB) with a direct influence path coefficient, namely 0.441 work environment variables affect (OCB) with a direct influence path coefficient of 0.408. Then the workload with a direct influence path coefficient of 0.396, while the motivational variable affects performance with a direct influence path coefficient of 0.317, the work environment variable affects performance with a direct influence path coefficient of 0.262, and the variable (OCB) affects performance with a path coefficient direct effect is 0.344.